Strengthening Integrated Mutual Understanding of Social Sciences Learning in Islamic Education Institutions: A Comparative Study in Madrasas, Islamic Boarding Schools and Integrated Islamic Schools in Bengkulu City - Irwan Satria; Budrianto Budrianto (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study aims to examine the role of social studies learning in strengthening mutual understanding among students in Islamic educational institutions in Bengkulu City. It explores how Islamic values, cultural integration, and national principles can be used as foundations to promote harmony and social cohesion within diverse educational contexts. Methodology: A case study approach with a multiple-case type was employed, guided by Yin’s design of connecting data with theoretical propositions. The study began with theoretical propositions to shape the research framework, aligning data collection and analysis with pattern-matching techniques. Data were gathered through interviews, classroom observations, and document analysis, focusing on social studies teachers' practices and perspectives in three Islamic educational institutions. Main Findings: The findings reveal that social studies teachers universally emphasize the importance of mutual understanding as a core objective in their teaching. They integrate Islamic principles, Pancasila (Indonesia's foundational philosophy), and local culture to foster tolerance, empathy, and collaboration among students. Teachers adopt diverse learning models and approaches, including discussion-based, problem-solving, and project-based learning, to contextualize lessons and encourage critical engagement. These strategies have significantly promoted mutual understanding and reduced social prejudices within the student body. Novelty/Originality of the Study: This study uniquely highlights the strategic role of Islamic educational institutions in using social studies learning to strengthen mutual understanding. By connecting religion, national values, and cultural heritage, the study provides new insights into the transformative potential of education in shaping harmonious and inclusive communities, offering practical implications for policymakers and educators.